Pivoting to Childbirth at Home or in Freestanding Birth Centers1 in the US During COVID-19: Safety, Economics and Logistics - Daviss, Betty-Anne; Anderson, David A.; Johnson, Kenneth C. (Frontiers in Sociology, 2021)
Birth-related decisions always center on safety; giving birth during a pandemic brings safety challenges to a new level. Amid the COVID-19 crisis, the concurrent work furloughs, business failures, and mounting public and private debt have made prudent expenditures an inescapable second concern. This article examines the intersection of safety and economic efficiency that became critical as the novel coronavirus ravaged bodies and economies around the world. Those interests, and the solutions discussed in this article, remain important even in less troubled times. Without compromising safety, having an additional 10% of deliveries take place in homes or freestanding birth centers could save almost $11 billion per year in the United States.